The Impact of Product Market Reforms on Firm Productivity in Italy - Lanau, Sergi (IMF Working Papers; Working Paper ;, 2016)
This paper examines the role of removing obstacles to competition in product markets in raising growth and productivity. Using firm-level data from Italy during 2003-13 and OECD measures of product market regulation, we estimate the effect of deregulation in network sectors on value added and productivity of firms in these sectors, as well as firms using these intermediates in their production processes. We find evidence of a significant positive impact. These effects are more pronounced in Italian provinces with more efficient public administration, underscoring the complementarities of advancing public administration and product market reforms simultaneously.